Pendekatan Literasi Digital Berbasis Website Dalam Pengelolaan Desa Wisata Wasuemba Kabupaten Buton - Andy Arya Maulana Wijaya; L.M Azhar Sa'ban; Muhammad Hidayatullah; Laode Arwan; Jasti Jahami; Putri Mawangsari; Narwati Narwati; Fadel Arroyan; Nirmala Sari Anwar (Universitas Muhammadiyah Sidenreng Rappang, 2025)
The Digital Literacy Action Program Based on a Website in Wasuemba Tourism Village, Buton Regency, is a community empowerment initiative to address limited digital literacy and underdeveloped tourism promotion. Despite being listed in the Top 100 ADWI 2024, marine, cultural, and local product potentials have not significantly improved community welfare due to inadequate internet infrastructure, low digital skills, and reliance on simple social media content. This program, implemented by Universitas Muhammadiyah Buton with Pokdarwis Lahonduru, involved socialization, management training, the development of an official village website (https://wasuemba-desa.id), Starlink internet installation, and digital content workshops. Results indicate improved digital literacy, with participants’ understanding rising from 38% (pre-test) to 60% highly proficient (post-test). Academically, the program contributes a community-based digital literacy model for tourism village development. Socio-economically, it fosters community participation, broadens promotion, increases tourist visits, and creates new entrepreneurial opportunities. Hence, the program emphasizes the importance of integrating digital literacy, infrastructure, and community participation to enhance rural tourism competitiveness in the digital era.